Antecedent Variables that Influence Alfamidi Semarang Consumers' Purchasing Decisions (Study on Semarang Alfamidi Consumers) - Maulana, Faisal Arif; Mahmud, Mahmud (Universitas Negeri Semarang, 2024)
The aim of this research is to examine the influence of corporate social responsibility, social media marketing, shop area, sales promotions, and the value of profits experienced on purchasing decisions at Alfamidi minimarkets. This type of research is quantitative and the information collected comes from AlfaMidi consumers. The population of this research is 109 AlfaMidi visitors. The sampling technique uses accidental sampling. The results of partial t-hypothesis testing, store environment variables and profit value have an influence on purchasing decisions, while CSR variables, social media marketing variables and sales promotion variables have no influence on purchasing decisions.